2022
DOI: 10.1111/jsap.13568
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an intervention of exercise on sleep and seizure frequency in idiopathic epileptic dogs

Abstract: Objective The goal of this study was to compare sleep and seizure frequency between epileptic dogs prescribed a 20% activity increase and epileptic dogs not prescribed an activity increase. Methods Sixty‐nine dogs receiving anti‐epileptic drug therapy were enrolled in a 6‐month prospective, randomised, placebo‐controlled clinical trial with an intention‐to‐treat analysis. A canine activity monitoring device was used to measure activity levels and sleep scores. Results Using an intention‐to‐treat analysis, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 48 publications
(116 reference statements)
0
6
0
Order By: Relevance
“…These findings are consistent with our recent interventional study on the effect of assigned exercise as adjunct therapy in dogs with epilepsy that were refractory to AED treatments. In that study, we found a significant increase in the number of seizures and seizure-days per month in dogs that were assigned and completed at least a 10% increase in activity (Grady et al 2023).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…These findings are consistent with our recent interventional study on the effect of assigned exercise as adjunct therapy in dogs with epilepsy that were refractory to AED treatments. In that study, we found a significant increase in the number of seizures and seizure-days per month in dogs that were assigned and completed at least a 10% increase in activity (Grady et al 2023).…”
Section: Discussionmentioning
confidence: 75%
“…In that study, we found a significant increase in the number of seizures and seizure‐days per month in dogs that were assigned and completed at least a 10% increase in activity (Grady et al . 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In canine patients, epilepsy was found to be the most prevalent chronic neurological disorder ( 3 , 4 ). Although the exact point prevalence is not known, this was estimated to be between 0.6 and 0.75% in the general dog population ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Idiopathic epilepsy (IE), which can be further subclassified into genetic epilepsy, suspected genetic epilepsy or IE of unknown cause, is the most common cause responsible for seizures in dogs ( 1 , 4 ). Seizures can also be a consequence of intracranial disease (structural epilepsy), metabolic disorders or intoxication (reactive seizures) ( 6 ).…”
Section: Introductionmentioning
confidence: 99%